REGULATORY TRANSCRIPTION FACTORS MAY PARTICIPATE IN POST-INITIATION CONTROL OF TRANSCRIPTION - V. M. Merkulov; T. I. Merkulova (Вавиловский журнал генетики и селекции, 2015)
Sequence-specific (regulatory) transcription factors selectively regulate the transcription levels of different sets of eukaryotic genes depending on cell type, developmental stage, and external signals. Recruitment of the RNA-polymerase II transcription initiation apparatus to promoters by regulatory transcription factors is generally recognized as the key mechanism responsible for transcription control by these proteins. However, recent data indicate that regulatory transcription factors may also be involved in transcription elongation control. These data are summarized here.